-100=-2(1+7m)

Simple and best practice solution for -100=-2(1+7m) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -100=-2(1+7m) equation:


Simplifying
-100 = -2(1 + 7m)
-100 = (1 * -2 + 7m * -2)
-100 = (-2 + -14m)

Solving
-100 = -2 + -14m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '14m' to each side of the equation.
-100 + 14m = -2 + -14m + 14m

Combine like terms: -14m + 14m = 0
-100 + 14m = -2 + 0
-100 + 14m = -2

Add '100' to each side of the equation.
-100 + 100 + 14m = -2 + 100

Combine like terms: -100 + 100 = 0
0 + 14m = -2 + 100
14m = -2 + 100

Combine like terms: -2 + 100 = 98
14m = 98

Divide each side by '14'.
m = 7

Simplifying
m = 7

See similar equations:

| 32=2y+8 | | 5+5+6+4+x=23 | | 12-3/5x=-27 | | -9-(8-5d)=18 | | N-(50)=-31 | | 4a-2a=-36 | | 2(-4)+2x=-6x-2 | | 3d+8=-17 | | 120+2y=180 | | 10+7+4=10+7+4 | | P+1-2=7 | | 63=3k | | 6(2X-5)-(3-5X)= | | 4(6x+6)= | | 7a+1-3a-5=3[a+1] | | 9cosx+1=8cosx | | 7n-6n=-6 | | 5/7=x/7000 | | Log(2x+1)=3x-2 | | 1(2+3)=2+3 | | (2t+10)(3s)=180 | | (-5x-1)+2x+3=-4x+5 | | 2(-5x+3)-5x-4=-x+58 | | -8(x+5)=-8x-5(x+5) | | Nz-a=bx+d | | 5x+3x+2=10 | | 5x-17=4z-36 | | -1-3(x+2)=-5x-15 | | -8(x+5)=-8x-(x+5) | | 3-5(-x+1)=-x-8 | | 17x-29y=7 | | -7X-8(4X+5)=6X-9 |

Equations solver categories